TRANSFORMATION OF NATIONAL HISTORY IN THE SECOND HALF OF XVIII-th - THE FIRST THIRD OF THE XIX-th CENTURY - A. F. Bayteryakova; S. I. Malovichko (Гуманитарные и юридические исследования)
The paper studies the problem of the transformation of construction practice as regards the past of the nation-state in the second half of 18th - the first third of the 19th century. Comparative analysis of «grand narrative» texts on national past of the 18th century and the national-state narratives of the 19th century revealed the main lines showing the difference n historical description of the nation-state. The latter include readership, professionalizing of historiography, special focus on one's «own» nation-state, development of «the European canon», etc.